Topological nature of the node-arc semimetal PtSn4 probed by de Haas-van Alphen quantum oscillations. (16th March 2018) - Wang, Y J; Liang, D D; Ge, M; Yang, J; Gong, J X; Luo, L; Pi, L; Zhu, W K; Zhang, C J; Zhang, Y H
Abstract: Dirac node arc semimetal state is a new topological quantum state which is proposed to exist in PtSn4 (Wu et al 2016 Dirac node arcs in PtSn4 Nat. Phys .12 667–71). We present a systematic de Haas-van Alphen quantum oscillation study on this compound. Two intriguing oscillation branches, i.e. F 1 and F 2, are detected in the fast Fourier transformation spectra, both of which are characterized to possess tiny effective mass and ultrahigh quantum mobility. And the F 2 branch exhibits an angle-dependent nontrivial Berry phase. The features are consistent with the existence of the node arc semimetal state and shed new light on its complicated Fermi surfaces and topological nature.